Remanufacture of hot forging tools and dies using laser metal deposition with powder and a hard-facing alloy Stellite 21® - Jim Foster; Crawford Cullen; Stephen Fitzpatrick; Grant Payne; Liza Hall; James Marashi (Journal of Remanufacturing, 2019)
Additive Layer Manufacturing (ALM) processes are attracting interest in the forging industry due to their potential suitability for remanufacturing and repair of tools and dies. The ALM process known as Laser Metal Deposition with powder (LMD-p) can be used to provide a hard-facing alloy repair to hot forging tools. This is particularly important on complex tool geometries due their superior wear resistance. The Advanced Forming Research Centre (AFRC) has established a low cost standard test method to evaluate abrasive and adhesive wear on hot forging H13 tool steel dies on an industrial scale 160~kJ Schuler screw press. The bespoke tool design allows researchers to benchmark new and novel coatings, lubricants and additive layers against a known standard. Furthermore, AFRC metrology standard methods ensure repeatability and reproducibility of benchmark results. To evaluate the performance of LMD-p for remanufacturing of hot forging tools and dies, a cobalt based alloy (Stellite 21®) was selected. Stellite 21® is widely used as a hard-facing alloy as it provides excellent machinability coupled with superior wear characteristics. AFRC standard dies were coated with LMD-p Stellite 21®. The LMD-p coating was then machined to final geometry and then subjected to hot forging under AFRC standard conditions to compare to benchmark wear characteristics. Adhesive and abrasive wear was evaluated. It was shown that the Stellite 21® LMD-p additive layer performed better in both adhesive and abrasive conditions than standard H13 tools steel dies.
Keywords: 650; Remanufacture; Additive layer.Laser metal deposition; Forging; Stellite 21®; H13; Tooling; Dies